2022
DOI: 10.2147/prbm.s363433
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Emotion Regulation on Non-Suicidal Self-Injury Among Adolescents: The Mediating Roles of Sleep, Exercise, and Social Support

Abstract: Purpose To explore the relationship between adolescents’ emotion regulation ability and non-suicidal self-injury (NSSI) behavior and the role of sleep, exercise, and social support in this relationship. Methods A total of 2573 adolescents were investigated with the Cognitive Emotion Regulation Scale, the Social Support Scale for Children and Adolescents, the Ottawa Self-Injury Questionnaire, and the Self-Made Living Condition Questionnaire, and path analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Incorporate a diverse range of age-appropriate aerobic, strength, and flexibility exercises into a weekly routine and school-based P.E. classes to improve overall physical and mental health [ 23 ] 5. Ensure daily consumption of a nutrient-dense breakfast, comprising whole grains, fruits, and protein, which has been linked to enhanced cognitive function, mood regulation, and reduced impulsivity [ 37 , 41 ] 6.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Incorporate a diverse range of age-appropriate aerobic, strength, and flexibility exercises into a weekly routine and school-based P.E. classes to improve overall physical and mental health [ 23 ] 5. Ensure daily consumption of a nutrient-dense breakfast, comprising whole grains, fruits, and protein, which has been linked to enhanced cognitive function, mood regulation, and reduced impulsivity [ 37 , 41 ] 6.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Among the most prevalent mental health problems among adolescents is non-suicidal self-injury (NSSI), which has been shown to be strongly related to difficulties in ER [23][24][25]. NSSI is defined as "the deliberate, non-fatal self-infliction of body tissue damage without suicidal intent" [26], and is associated with adverse outcomes, including diminished academic performance, peer-related difficulties, and an elevated risk of suicidal behaviors [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, poor sleep quality may damage adolescent emotional regulation, increase the risk of depression, and further increase the risk of NSSI [18]. Multiple studies have demonstrated that poor sleep quality significantly predicts adolescent NSSI [19][20][21]. Moreover, some studies have indicated that sleep quality acts as a mediator in the relationship between stressful experiences and suicidality [22,23].…”
Section: Introductionmentioning
confidence: 99%